Hubungan Lingkungan Kerja dengan Komitmen Organisasi pada Kantor Desa Ugi Kecamatan Sabbangparu Kabupaten Wajo - Yuliana Yuliana; Iwan Mamminanga; Sofyan Marzuki (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research was carried out at the Ugi Village Office, Sabbangparu District, Wajo Regency. The research will begin from March to June 2024. This research aims to determine the work environment of employees at the Ugi Village Office, Sabbanparu District, Wajo Regency, to determine organizational commitment at the Ugi Village Office, Sabbangparu District, Wajo Regency, and to determine the relationship between the work environment and organizational commitment at the Office. Ugi Village, Sabbangparu District, Wajo Regency. The method used is a census type with a quantitative associative approach. The results of this research show that the work environment carried out at the Ugi Village Office, Sabbangparu Subdistrict, Wajo Regency, has a score of 297 and is included in the good category of the average ideal score in the dimensions of the physical work environment and non-physical work environment. Organizational commitment at the Ugi Village Office, Sabbangparu District, Wajo Regency is included in the good category with a score of 361 from the average ideal score. This can be seen from the dimensions of organizational commitment based on personal, job characteristics, structural characteristics and work experience. To find out that the work environment has a positive and significant relationship to organizational commitment at the Ugi Village Office, Sabbangparu District, Wajo Regency.